Screening of Endophytes from Traditionally Used Medicinal Plants of Manipur for Their Antimicrobial Activity: An Impact towards Future Drug Discovery - Ngashangva, Ng; Devi S, Indira; M. C., Kalita (International Journal of Scientific Research in Biological Sciences, 2019)
Antimicrobial resistance has been developing fast and continuing to challenge the world medical sector. New strategies are needed to address this challenge that is incurring huge loss on human life. Medicinal plants from the untapped rainforest of the North-East India has a huge potential to find microbes that produce novel biomolecules. Bioactive endophytes were isolated from traditionally used medicinal plants. Paenibacillus spp. from Piscidia spp. in a fermentation broth has shown strong and broad-spectrum of activity at the range of 1600 AU/ml. Unexplored region has huge prospect to find novel biomolecules which can be harvested in scientific, economical and environmentally friendly. Moreover, it has shown that the traditional medicinal plant harboured bioactive. Moreover, it will provide insights into its metabolic potential and ecological role of this species